Age and residency duration of loggerhead turtles at a North Pacific bycatch hotspot using skeletochronology. (June 2015) - Turner Tomaszewicz, Calandra N.; Seminoff, Jeffrey A.; Avens, Larisa; Goshe, Lisa R.; Peckham, S. Hoyt; Rguez-Baron, Juan M.; Bickerman, Kalyn; Kurle, Carolyn M.
Graphical abstract: Highlights: Loggerhead demographic data off Baja, Mexico are important for turtle management. We apply skeletochronology to estimate residency duration and age-at-maturation. Dead-stranded juvenile turtles at this foraging site ranged from 3 to 24 years old. We estimate residency duration >20 years, and age-at-maturation ∼25 years old. Ongoing management to reduce fishery bycatch at this foraging hotspot is critical. Abstract: For migratory marine animals, like sea turtles, effective conservation can be challenging because key demographic information such as duration of life stages and exposure to spatially explicit threats in different habitats are often unknown. In the eastern Pacific near the Baja California Peninsula (BCP), Mexico, tens of thousands of endangered North Pacific loggerhead sea turtles ( Caretta caretta ) concentrate at a foraging area known to have high rates of fishery bycatch. Because stage survivorship of loggerheads in the BCP will vary significantly depending on the number of years spent in this region, we applied skeletochronology to empirically estimate residency duration in this loggerhead hotspot. The observed age distribution obtained from skeletochronology analysis of 146 dead-stranded loggerheads ranged from three to 24 years old, suggesting a BCP residency of >20 years. Given the maximum estimated age and a one-year migration to western Pacific nesting beaches, we infer age-at-maturation for BCP loggerheads at ∼25 years old. We also examine survivorship at varying BCP residency durations by applying our findings to current annual mortality estimates. Predicted survivorship of loggerheads spending over 20 years in this BCP foraging habitat is less than 10%, and given that ∼43, 000 loggerhead turtles forage here, a significant number of turtles are at extreme risk in this region. This is the first empirical evidence supporting estimated age-at-maturation for BCP North Pacific loggerheads, and the first estimates of BCP stage survivorship. Our findings emphasize the urgent need for continued and effective international conservation efforts to minimize bycatch of this endangered species.